Pengaruh Pemahaman Pencatatan Akuntansi Dan Kesiapan Modal Terhadap Efesiensi Pendapatan Usaha Sembako: Studi Kasus Usaha Sembako Kecamatan Bayung Lencir - Nurkhasanah Nurkhasanah; Eka Julianti Efris Saputri; Aditya Pradana; Kiki Helencia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
To determine the influence of understanding accounting and capital readiness on the efficiency of basic food business income. Quantitative is a research method that uses data in the form of numbers and the collected data is analyzed using statistical formulas. The population that will be used in this research is MSME actors, especially basic food businesses registered with the Bayung Lencir District Cooperatives, Small and Medium Enterprises Service, totaling 100 MSME business actors. The classical assumption test is a prerequisite for multiple regression analysis, this test must be influenced so that the estimates of parameters and regression coefficients are not biased. In testing this class of assumptions, namely the normality test, multicollinearity test, heteroscedasticity test, autocorrelation test. Partially, accounting records have a more dominant influence than capital readiness in increasing income efficiency. This shows that understanding accounting records is very influential in increasing revenue efficiency and business sustainability, because by understanding accounting records, business actors can manage business finances and make decisions about managing their business easily.